Probiotics and their mechanism of action in animal feed - Molina, Andrea (2019)
Introduction. In the livestock production for commercial purposes, additives are frequently used to increase the effectiveness of nutrients present in the food, its availability, and absorption in the gastrointestinal tract, as well as modulate the intestinal flora of animals and promote their growth and productivity. Antibiotics have been among the most used additives in recent decades animal production worldwide. Objective. The aim of this literature review was to describe the use of probiotics as additives in animal nutrition, as an alternative to the use of antibiotics as growth promoters in commercial livestock production. Development. This compilation analyzes the current definition of probiotics accepted by the Food and Agriculture Organization of the United Nations (FAO) and the World Health Organization (WHO) it also describres the microorganisms allowed as probiotics in animal nutrition in Costa Rica and the United States. Additionally,the main mechanisms of action in productive animals are explained. Probiotics are living organisms that when administered in adequate amounts confer a benefit to the health of the host, this effect must be proven and overcome the effect given by the placebo. The microorganisms used as probiotics in animal nutrition should not be pathogenic for animals, and should be resistant to the processes of food and feed elaboration. It has been reported that the benefit of probiotics in productive animals is mainly due to the fact that these promote the microbial balance in the digestive tract and the modulation of the immune system, resulting in an increase in the digestion and absorption of nutrients and decreasing the incidence of infectious diseases. Conclusion. The use of different probiotics in productive animals to increase productivity and animal health, has been proven in different commercial livestock species and its use is promising as a growth promoter instead of antibiotics.